Exchange rate regimes, foreign exchange volatility and export performance in Central and Eastern Europe: just another blur project? - Balázs Égert; Amalia Morales-Zumaquero (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
This paper attempts to analyze the direct impact of exchange rate volatility on the export performance of ten Central and Eastern European transition economies as well as its indirect impact via changes in exchange rate regimes.Not only aggregate but also bilateral and sectoral export flows are studied.To this end, we first analyze shifts in exchange rate volatility linked to changes in the exchange rate regimes and second, use these changes to construct dummy variables we include in our export function.The results suggest that the size and the direction of the impact of forex volatility and of regime changes on exports vary considerably across sectors and countries and that they may be related to specific periods.
URN:NBN:fi:bof-201408072036
Keywords: F31; 330; exchange rate volatility; export; trade; transition; structural breaks